INVESTMENT OPPORTUNITY SET, MULTIPLE LARGE SHAREHOLDER AND CAPITAL STRUCTURE ON DIVIDEN POLICY THROUGH LIKUIDITY (Study On Manufacturing Companies Listed On The Indonesian Stock Exchange) - Udyono Udyono (Scientia Integritas Utama, 2022)
This study aims to determine the effect of Investment Opportunity Set, Multiple Large Shareholders and Capital Structure on Dividend Policy through Liquidity in Manufacturing Companies in Indonesia. This study uses secondary data by taking data from annual reports and financial statements of manufacturing companies listed on the Indonesia Stock Exchange, namely www.idx.co.id. The sampling technique in this study was purposive sampling so that the number of samples used was 41 with 123 observational data. The data analysis technique in this study used Multiple Linear Regression Analysis and Moderate Regression Analysis (MRA) using SPSS assistance which was directed to answer the formula problems or hypotheses that have been formulated in this study and are used to examine the relationship between Investment Opportunity Set, Multiple Large Shareholders and Capital Structure variables on Dividend Policy and Liquidity as a moderating variable in manufacturing companies in Indonesia. The results of this study indicate that Investment Opportunity Set has a significant positive effect on Dividend Policy, Multiple Large Shareholders has a significant negative effect on Dividend Policy and Capital Structure has a significant positive effect on Dividend Policy. In addition, the results of the study using the Moderate Regression Analysis (MRA) test show that Liquidity moderates the relationship between Investment Opportunity Sets and Dividend Policy, Liquidity moderates the relationship between Multiple Large Shareholders and Dividend Policy, and Liquidity also moderates the relationship between Capital Structure and Dividend Policy.